2015
DOI: 10.5897/ajfs2014.1207
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional potential of yam chips (Dioscorea cayenensis and Dioscorea rotundata Poir) obtained using two methods of production in Togo

Abstract: Yam is one of the most staple foods in West African countries and provides an important part of the energetic for people. This study examines chemical composition of Dioscorea cayenensis and Dioscorea rotundata Poir species dried yam chips obtained using two methods of production in Togo. Three local varieties of yams (Koukou, Kéki and Laboco) were processed in chips and were sun dried (at 28-30°C) or oven-dried (at 50°C). Nutritive components (carbohydrates, protein fats, mineral salt, vitamin C and anti-nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…However, varying ranges of values were reported for laboratory processed yam chips and flour samples. Values smaller than those obtained in this study were reported by Abioye (2012) (2.6-2.9%), Adejumo et al (2013) (2.4-2.6%) and Djeri et al (2015) (3.5-5.7%). However, all these authors used Dioscorea cayennensis subsp.…”
Section: Compositioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, varying ranges of values were reported for laboratory processed yam chips and flour samples. Values smaller than those obtained in this study were reported by Abioye (2012) (2.6-2.9%), Adejumo et al (2013) (2.4-2.6%) and Djeri et al (2015) (3.5-5.7%). However, all these authors used Dioscorea cayennensis subsp.…”
Section: Compositioncontrasting
confidence: 74%
“…The impact of cooking on the proximate composition of water yam has also been discussed in terms of moisture, protein, carbohydrate, fibre, fat, ash and gross energy (Ezeocha and Ojimelukwe 2012). Some studies have also investigated the effect of processing conditions on the nutritional composition and functional properties of laboratory processed yam chips (Djeri et al 2015) and flour (Abioye 2012;Adejumo et al 2013;Obadina et al 2014;Ajala and Idowu 2016). Only one study, on the other hand, is available on the assessment of the effect of storage duration on the nutritional composition of yam chips from Itamerin market (Oyo state, Nigeria) (Jonathan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yam (Dioscorea spp) is an important multi-species tropical tuber crop that has about 600 known species (Obidiegwu and Akpabio, 2017). The most economically important species grown are white yam (Dioscorea rotundata), yellow yam (Dioscorea cayenensis), water yam (Dioscorea alata), Chinese yam (Dioscorea esculenta) aerial yam (Dioscorea bulbifera) and trifolate yam (Dioscorea dumentorum) (Djeri et al, 2015). Of all these important species, the white yam (Dioscorea rotundata) is the most preferred and widely grown specie in West Africa.…”
Section: Introductionmentioning
confidence: 99%